Tinjauan Yuridis Sosiologis Terhadap Meningkatnya Kekerasan dengan Menggunakan Senjata Api - CH. Medi Suharyono (Jurnal Hukum IUS QUIA IUSTUM, 2012)
This research was conducted to find out the sociological juridical reasons on the increase of crimes using firearm. This is a socio legal research. The research result showed that sociologically the increase of firearm ownership in the society has resulted in the increasing number of crimes using firearm in the society. One of the reasons is that the law permits firearm ownership through two gates, by the Minister or by the Police.